Growth Kinetics of Gold Nanoparticles via P-Fuzzy Systems - Wasques, Vinícius F. [UNESP]; Marangoni, Valéria Spolon; Anghinoni, Shaian José (Springer Nature, 2023)
This article presents an application of p-fuzzy systems to estimate the maximum absorption wavelength of gold nanopartcles, as well as the stability point during their growth kinects. The classification of the wavelength and absorption values are modeled by fuzzy sets. Two fuzzy rule-based systems are provided in this study. The first aims to estimate the curves of wavelength by absorption. The second has the purpose of estimating the maximum absorbance with respect to time. The numerical method incorporated in the p-fuzzy system is the Euler’s method, where the direction field is replaced by the output produced by the fuzzy rule-based system. For these fuzzy rule-based systems the Mamdani method is considered as the fuzzy inference. A simulation of the proposed method, considering a dataset of gold nanoparticles formation, is presented in order to validate the response provided by the p-fuzzy system.
Keywords: Chemical Reaction; Fuzzy Rule-Based Systems; Nanomaterials; P-fuzzy systems